Planning to improvise? The role of reasoning in the strategy process: Evidence from Malaysia - Hughes, Paul (Springer US, 2018)
Planning and improvisation are depicted as alternate decision-making orientations in the strategy process literature, executed by two parallel cognitive contexts: rational or intuitive, but can rationality and intuition be harmonized in the strategy process? Strategic managers may not have to choose to either plan or improvise, rather there is a need to shift the focus of research from such trade-offs to paradoxical thinking.Drawing on survey data from Malaysian research-intensive firms, we investigate how strategy develops through managers’ strategic reasoning under key external (market turbulence) and internal (centralization, manager level) contingencies.In contrast to common assumptions in the management literature, we find that both rational and intuitive reasoning can drive planning and improvisation for firms in emerging economies, with additional positive moderation effects under centralization and manager level. Firms that achieve high levels of both planning and improvisation concurrently are characterized by significantly greater rationality relative to the high planning group and the high improvisation group. The findings extend strategy process research, highlighting how firms in emerging economies differ from theory derived from developed economies.